Knowledge and practices regarding household air pollution in communities of slum areas of Sonipat district in Haryana - Singh, Khajan; Singh, Mahender; Jha, Sanjay Kumar; ., Preeti; Aggarwal, S. K. (International Journal Of Community Medicine And Public Health, 2020)
Background: Each year globally, 3.8 million people die prematurely from illness attributable to the household air pollution. We assessed community knowledge and practices regarding household air pollution in slum areas of Sonepat district in Haryana. Methods: A community-based cross-sectional study was conducted among 104 households in slum areas of Sonepat district. Data were collected using semi-structured questionnaire included socio-demographic profile, questions for knowledge and practice regarding indoor pollution. The data were coded and analysed using the software R, version 3.6.2. Results: Of 104 household heads interviewed, 82.7 % were males and 17.3% were females. Most (69.2%) of the respondents were illiterate. More than half of the participants (53.8%) were labourer and rest were factory workers. Two third (75%) and more (79.8%) of the head households were aware that cooking fuel was harmful for the environment and smoke was harmful to the health respectively. Two third (75%) were not aware about Pradhan Mantri Ujjwala Yojana. Types of fuel used for cooking revealed that 71.2% and 21.1% of households used LPG and charcoal/firewood, respectively and (73.1%) of household cooked food inside the house. Conclusions: The slum communities are aware of indoor air pollution and have knowledge regarding possible health effects. They are exposed to air pollution arising from cooking fuels. There is need for promoting awareness on exposure reductions in homes. The results of our study may help policymakers understand the need for strengthening supply of LPG under Pradhan Mantri Ujjwala Yojana.